Propagation of Dendrobium antennatum Lindl via Seed Culture In Vitro Using Simple Medium: Fertilizer and Complex Organic Based Medium - Julius Dwi Nugroho; Agustina Yohana Setyarini Arobaya; Evelyn Anggelina Tanur (Bogor Agricultural University, Indonesia, 2019)
A New Guinea Orchid, Dendrobium antennatum Lindl urgently needs to conserve. The availability of in vitro germination technique for this orchids is significantly important to present the useful tool for conservation effort. This study aimed to find a simple media that consists of Growmore 10-55-10, a foliar fertilizer and complex organic i.e. coconut water, banana pulp, onion spring extract, and carrot juice. Five in vitro medium for seed germination and four in vitro sub-culture medium for planlet growth were formulated and used in this study. Our findings revealed that seed germination in vitro of Dendrobium antennatum well occured on the medium of Growmore 10-55-10 supplemented with 10% coconut water (GCw) and of Growmore 10-55-10 supplemented with 50 g/l extract spring onion. The seed germination process from sowing the seed to plantlet production ready to transfer to sub-culture medium for further growth took time 140 days. The embryo became pale green at the day 11 on the germination media. It could be used as a tool for detection of viability of the seeds. Both seed germination medium could be used also as sub-culture medium for enhancing the growth of the plantlets but not for multiplication of shoots.